Wireless Sensor Network (WSN) in Insect Monitoring: Acoustic Technique in Insect Monitoring (A Review/Survey) - Saleh, Yusuf; Sani Yahya, Muhammad; Abdul Dalyop, Ishaq; Hussain, Rashid (International Journal of Engineering and Technology, 2018)
Eco-friendly and effective method of white grub control is needed to reduce the impact of pesticide on the environment and the cost of control.Â The use of nematode as a biological agent to control larvae under soil was positive. The challenge is about the accuracy in time, location and amount of biological control agent required for control at initial infestation of the harmful insects, to reduce the damage the use of wireless sensor network (WSN) is required. Work carried out, sent at a threshold value of CO2 under the soil determine from lab to greenhouse to open field experiments. Initial stage detection of these insects life cycle is required for accurate time and location for control of these insect pests for resource effectiveness. This location can be communicated to a mobile phone via Global System for Mobile Communication (GSM) with Global Packet Radio Service modules (GPRS). Next challenge is to quantify the CO2 level from the white grubs as part of soil respiration, and to estimate their population. The farmers could be trained as listeners to survey for acoustic evidence of insects and to identify them by distinctive spectral and temporal pattern. Acoustic detection can be used to estimate the population of white grubs. A hypothesis of 90% success of the combination of CO2 burstsensing from white grubs (GMM221 sensor) as a generic signal with volatile compound as a specific signal from plant roots under insect attack and using Laboratory Virtual Instrument Engineering Workbench (LabVIEW) is considered. In the future, a universal sensor is to be developed for high accuracy with LabVIEW monitoring interface.Â Â